Comparative Assessment of Soil Fertility Status of Aged and Abandoned Rumuolumeni Dumpsite, Port Harcourt, Nigeria - Iyama, William Azuka; Timothy, Michael Nakara; Egbunefu, Chukwudi Omeni; Emejuru, Woroma Stella; Samuel-Harry, Fanny; Edori, Onisogen Simeon (European Journal of Applied Sciences, 2022)
The levels of pH and soil organic parameters around a solid waste dumpsite receiving untreated wastes from several sources though abandoned for over 10 years and a control site within Rumuolumeni, Port Harcourt, Nigeria was assessed. The top soil of depth, 0–15cm was collected and analysed for pH and alkalinity values, conductivity, total nitrogen, moisture content, total organic carbon (TOC), total organic matter (TOM), and available phosphorus using standard methods. The results were; pH (2.62±0.00 -6.52±0.00), electrical conductivity, EC, µS/) (850±4.95 -1088±1.00), % moisture content (21.51±0.00 -24.74±0.00), % total organic carbon, TOC (2.22±0.02 -3.68±0.02), % total organic matter, TOM (3.396±0.00 -6.393±0.00), % total nitrogen (0.110±0.00 -0.186±0.00), % Phosphorus (1.360±0.00 -2.216±0.00) and alkalinity, mg/kg as 3.816±0.00 -8.15±0.00). The results showed that the waste dump contributed to the high levels of nutrients and heavy metals. The % spatial variation showed pH, % moisture content, TOC, % total nitrogen, % P above 90% for station A while Conductivity, % moisture content, TOM for station B and conductivity, % moisture content and TOM for station C were also above 90%. The % variation from the control also indicate that station B for pH, TOC and alkalinity were above 90 % whereas in station A, only % total nitrogen (7.46%) and B (5.46%) were below 10 %. This is an indication of depletion in % nitrogen and the pH, alkalinity of the study soil is of toxic level for good soil fertility. The ANOVA result showed that there was no significant difference in the spatial fertility level for the organic parameters (P<0.05). There is need to control planting on this soil locations due to the acidic levels and organic matter contents which have been affected by age, leaching and demineralization processes.